World Athletics and IIRM form outbreak prevention taskforce for mass events (Worldathletics, 2020)
World Athletics has joined forces with the International Institute for Race Medicine (IIRM) to set up a medical taskforce to provide endurance events that include mass gatherings with guidelines for outbreak prevention.